Gender Awareness in Restructuring the English Courses in Nepal - Kshetree, Arun Kumar (Kaladarpan कलादर्पण, 2022)
The courses and curricula get changed with the changes occur in the society which cause the change in the objectives and aims of studying the courses. This paper is based on the content analysis of the BBS First Year English course of Tribhuvan University of Nepal from feminist perspective. It intends to raise gender awareness in teachers, students and course designers as well. I have tried to analyse the recommended reading texts in the course from feminist viewpoint. In fact the textbooks provide guidelines for both teachers and students and play a vital role in shaping students’ behaviors and ideology. So, the textbooks should be analyzed to explore the potential impact they make upon students. The study was executed to explore the representation of males and females in terms of status, roles, occupations and activities in BBS first year English textbook of TU which was revised and implemented from this year. For this the texts were studied and analysed from the feminist viewpoint. The results showed that the newly revised course of BBS first year English was, to some extent, successful in maintaining gender balance by selecting reasonable number of female writers and the text elated to female issues. There are texts which advocate the females’ issues in the society, their problems and rights etc. The texts raise the messages against different social evils and problems.